The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsami.9b05194
|View full text |Cite
|
Sign up to set email alerts
|

Opening and Closing of Particle Shells on Droplets via Electric Fields and Its Applications

Abstract: Active, tunable, and reversible opening and closing of particle shells on droplets may facilitate chemical reactions in droplets and enable various small-scale laboratory operations, including online detection, measurement, and adjustment of droplet liquid. Manipulating various types of particle shells in a controlled manner requires new routes. This work provides a new strategy for controlling the spatial arrangement of particle-covered oil droplets using electric fields that expands the application of respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Manipulating particles anchored on the droplet interface is one of the promised techniques for designing functional droplet. Using active structuring of a particle-covered droplet under the electric field, Rozynek et al demonstrated a millimeter-sized optical diaphragm [ 162 ] ( Figure 10 E). Li et al redistributed aluminum nanoparticles on an o/w emulsion droplet via an electric field for generating a Janus droplet [ 163 ] ( Figure 10 F).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulating particles anchored on the droplet interface is one of the promised techniques for designing functional droplet. Using active structuring of a particle-covered droplet under the electric field, Rozynek et al demonstrated a millimeter-sized optical diaphragm [ 162 ] ( Figure 10 E). Li et al redistributed aluminum nanoparticles on an o/w emulsion droplet via an electric field for generating a Janus droplet [ 163 ] ( Figure 10 F).…”
Section: Applicationsmentioning
confidence: 99%
“…( D ) Stabilizing the shape of deformed colloidal particles by the interfacial jamming of nanoparticles [ 121 ]. ( E ) Optical diaphragm based on the particle self-assembly [ 162 ]. ( F ) Generation of an aluminum Janus particle using an electric field [ 163 ].…”
Section: Figurementioning
confidence: 99%
“…14,15 Moreover, particle-covered droplets facilitate the fabrication of new materials [16][17][18] and can be designed to form novel adaptive structures. 19,20 Pickering droplets can also be used in basic research, e.g., as model systems for mimicking the physical properties of red blood cells 21 or for studying particle crystal growth and ordering or particle layer buckling on curved interfaces. [22][23][24][25][26] In many research areas, knowledge of the stability and mechanics of an individual Pickering droplet is essential, e.g., for the efficient fabrication of Pickering emulsions, 27 for designing emulsions with controlled stability, 28,29 and, in general, for the further development of the abovementioned research fields.…”
Section: Introductionmentioning
confidence: 99%
“…Along with other "smart" materials, ERFs are widely used in technology in various devices such as shock absorbers, control valves, dampers and in microfluidics, robotics, sensors, etc [2]. The modern applications of the ER effect include sensors for rapid plague diagnostics and nanodiaphragms with adjustable aperture [3,4]. The several qualities are essential to the wide practical application of ERFs, namely significant change of rheological properties under electric field, low conductivity, chemical, aggregate and thermal stability.…”
Section: Introductionmentioning
confidence: 99%